(untitled) (Research, Society and Development, 2021)
The production and consumption of cherry tomatoes (Solanum lycopersicum var. cesariforme) has been increasing due to its nutritional properties and gastronomic potential. However, there are few data reporting the intrinsic characteristics and health quality of cherry tomatoes sold in states in the North region of Brazil. The objective of this work was to evaluate the physicochemical properties and microbiological quality of cherry tomatoes commercialized in emporiums in the city of Manaus-AM. An amount of 10 cherry tomatoes was acquired in emporiums in the West (ZO) and Center South (ZCS) zone of Manaus. These fruits were evaluated for their physicochemical properties (moisture, pH, total soluble solids expressed in °Brix, titratable acidity expressed in citric acid and ratio) and microbiological quality (mold and yeast counts, Escherichia coli and evaluation of the presence of Salmonella sp.) The average moisture content was 94.74% and pH ranged from 5.44 (ZO4) to 4.87 (ZCS1). The significant content of total soluble solids (7.60 °Brix) was verified in the ZCS sample. The acidity in citric acid was, on average, 0.39%. The ratio values ​​ranged from 26.67 (ZO4) to 8.28 (ZO1). In the evaluation of sanitary quality, 2x102 CFU/g to 5 x 103 CFU/g counts were verified for molds and yeasts, but no contamination by E. coli and Salmonella sp. Cherry tomatoes sold in the city of Manaus can be sources of fungi producers of toxins and, therefore, the microbiological quality of these fruits must be monitored to prevent damage to consumer health.